Degradation mechanism and eco-toxicity assessment of bisphenol S based on peroxymonosulfate activated with Co3O4 surfaces. (20th March 2022) - Wang, Zehua; Lv, Guochun; Zhang, Chenxi; Sun, Xiaomin
Abstract: In this paper, the degradation mechanism and eco-toxicity assessment of bisphenol S (BPS) was studied in the aqueous environment based on the heterogeneous activation of peroxymonosulfate (PMS) through spinel tricobalt tetraoxide (Co3 O4 ) catalyst using density functional theory (DFT) and computational toxicology methods. The result indicates that (100) and (311) surfaces have the higher proportion of bivalent cobalt, the increase of charge transfer, negative adsorption energy, and the lower surface energy. They can more effectively promote the decomposition of PMS to generate reactive oxide species. When generated oxidants react with BPS, HO -addition reaction at the ortho -C atom-sites plays a dominant role in the system Co3 O4 /PMS. The presence of SO4 -, HO, and O2 promotes the formation of transformation intermediates and products. The formation pathways of important experimental intermediates hydroquinone, p -hydroxybenzenesulfonic acid, and 3, 4-dihydroxybenzenesulfonic acid are identified. And, some hydroxylation products that are not identified in the experiment are determined. The eco-toxicity evaluation shows that most of the decomposition products are completely harmless or significantly reduced compared to BPS. This study not only provides insights into the degradation mechanism of BPS in Co3 O4 /PMS system, but also is expected to be a guide for further experimental research and the design and optimization of the activated catalysts in sulfate radical-based advanced oxidation technologies. Graphical abstract: Image 1 Highlights: Co3 O4 (100) and (311) surfaces are more effectively promote the PMS decomposition. The most reactive-site of BPS is the ortho -C atom. OH.-initiated plays a dominant role in the degradation process of BPS, not SO4 - . Hydroquinone and p-hydroxybenzenesulfonic acid are important intermediates. Compared with BPS, most decomposition products are harmless or reduced.